On exact solutions of the (2+1)-dimensional time conformable Maccari system - Akar, Mutlu; Ozkan, Erdogan Mehmet (WORLD SCIENTIFIC PUBL CO PTE LTD, 2023)
For the (2+1)-dimensional time conformable Maccari system with beta-derivative, exact solutions are obtained in this paper using the improved sub-equation method. This technique has been used to find rational solutions, generalized hyperbolic function solutions and generalized trigonometric function solutions. The new structures of the solutions are shown after the proper parameter values have been given. It is easier to understand the intricate physical processes of these dynamical models by viewing the physical surfaces of some obtained solutions in various forms. The outcomes demonstrate the efficiency of the applied strategy, which may be used to solve a number of nonlinear physical problems. (2+1)-dimensional time conformable Maccari system is considered and the graphs of solutions are sketched using MAPLE software after its exact solutions which are acquired using the improved sub-equation method.
Keywords: Improved sub-equation method; (2+1)-dimensional time conformable Maccari system; beta-derivative; DIFFERENTIAL-EQUATIONS; MODEL; Physics